Evaluation and Comparison of Accuracy of Measuring the Position of Miniscrew Implants using Two-dimensional Orthopantomogram and a Three-dimensional Imaging with Direct Method on Dried Skull - R H Kamble; Sachin V Patil; P V Hazarey; Anil G Ghom (Wolters Kluwer Medknow Publications, 2011)
Introduction The accuracy of position of miniscrew implants is utmost important for implant success. In this study, we investigated whether the routine 2D ortopantomogram can be used to assess the accuracy in the placement of miniscrews as compared with 3D radiography and direct measurements on a dried skull. Methods: Miniscrew implants were placed in between premolar and molar areas at an angulation of 40΀ to 50΀ for maxilla and 10΀ to 20΀ for mandible on dried skull. Linear and angular measurements were taken on these dried skulls using direct method, ortopantomogram and 3D radiography. Analysis of variance (ANOVA) and multiple comparison Tukey's test were used to test for differences in three methods. Results: The results shows 20% vertical magnification for maxilla and mandible whereas horizontal measurements shows 54.2% of variations in maxilla and 27.1% of variations in mandible on panoramic radiographs as compared to direct method and 3D radiography. Angular measurements show 9΀ to 10΀ of variation on panoramic radiographs as compared to direct method and 3D radiography for both maxilla and mandible. Conclusion: Ortopantomogram shows more variations on linear and angular measurements as compared to direct method and 3D radiography whereas direct method and 3D radiography show no difference. But, we can calculate the angulations of miniscrew implant placement by angular regression model.